A Systematic Review of Emergency Department Use Among Cancer Patients. Issue 2 (March 2017) - Lash, Rebecca S.; Bell, Janice F.; Reed, Sarah C.; Poghosyan, Hermine; Rodgers, James; Kim, Katherine K.; Bold, Richard J.; Joseph, Jill G.
Abstract : Background: Recent reports call for reductions in costly and potentially avoidable services such as emergency department (ED) visits. Providing high-quality and safe care for oncology patients remains challenging for ED providers given the diversity of patients seeking care and the unpredictable clinical environment. While ED use by oncology patients is appropriate for acute health concerns, some ED visits may be preventable with well-coordinated care and adequate symptom management. Objective: The aim of this study was to summarize available evidence regarding the incidence, predictors of, and reasons for ED visits among oncology patients. Methods: Keyword/MeSH term searches were conducted using 4 online databases. Inclusion criteria were publication date between April 1, 2003, and December 5, 2014; sample size of 50 or more; and report of the incidence or predictors of ED use among oncology patients. Results: The 15 studies that met criteria varied in study aim, design, and time frames for calculating ED utilization rates. The incidence of ED visits among oncology patients ranged from 1% to 83%. The 30-day standardized visit rate incidence ranged from 1% to 12%. Collectively, the studies lack population-based estimates for all cancers combined. Conclusions: The studies included in this review suggest that rates of ED use among cancer patients exceed those of the general population. However, the extent of ED use by oncology patients and the reasons for ED visits remain understudied. Implications for Practice: Nurses are involved in the treatment of cancer, patient education, and symptom management. Nurses are well positioned to develop patient-centered treatment and care coordination plans to improve quality of care and reduce ED visits.